1974
DOI: 10.1037/h0035834
|View full text |Cite
|
Sign up to set email alerts
|

Influence of sex role stereotypes on personnel decisions.

Abstract: An in-basket exercise was used to investigate the influence of sex role stereotypes on the personnel decisions of 95 bank supervisors. The design consisted of four separate experiments (in-basket items) in which an employee's sex and other situational attributes were manipulated. Results confirmed the hypothesis that male administrators tend to discriminate against female employees in personnel decisions involving promotion, development, and supervision. Discrimination against male employees was found in perso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
75
0
1

Year Published

1981
1981
2013
2013

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 279 publications
(83 citation statements)
references
References 4 publications
7
75
0
1
Order By: Relevance
“…We can only speculate on the explanation for these findings Researchers have thoroughly documented the influence of sex stereotypes on a range of managerial selection, promotion, and compensation decisions (e.g., Gerdes & Gerber, 1983, Rosen & Jerdee, 1973, 1974Rosen & Mende, 1979). Perhaps sex stereotypes regarding what various male and female jobs are worth influenced choices among options for coping with labor shortages Recent research by Grams and Schwab (1985) illustrates how knowledge about the current market wage for a position influences the number of job evaluation points assigned to that position.…”
Section: Discussionmentioning
confidence: 99%
“…We can only speculate on the explanation for these findings Researchers have thoroughly documented the influence of sex stereotypes on a range of managerial selection, promotion, and compensation decisions (e.g., Gerdes & Gerber, 1983, Rosen & Jerdee, 1973, 1974Rosen & Mende, 1979). Perhaps sex stereotypes regarding what various male and female jobs are worth influenced choices among options for coping with labor shortages Recent research by Grams and Schwab (1985) illustrates how knowledge about the current market wage for a position influences the number of job evaluation points assigned to that position.…”
Section: Discussionmentioning
confidence: 99%
“…First, a strong preference for retirement may be perceived as a sign of low work motivation that may ultimately decrease productivity. Second, previous research into supervisors' support for early retirement indicates that supervisors tend to actively consider employees' personal circumstances and preferences (Rosen and Jerdee, 1974). Henkens, van Solinge, & Cozijnsen (2009), for instance, found that older worker's attitudes toward retirement played an important role in managers', but not business students' assessments of the desirability of retaining an older worker.…”
Section: Employee-level Characteristicsmentioning
confidence: 99%
“…In addition to the structural barriers that keep women from being hired (Rosen & Jerdee, 1974), it has been shown that young girls have less access to computers, both in school and at home, and therefore less of a chance to become skilled in using them (Hess & Miura, 1985). To compound this difficulty, most of the educational software available today is presented in a format that, while motivating and exciting for boys, probably discourages the girls who use it (Lepper & Malone, 1985).…”
Section: Sex Bias In Educational Software: the Effect Of Designers' Smentioning
confidence: 99%